'Render to Caesar the Things of Caesar and to God the Things of God': Recent Perspectives on a Puzzling Command (1945–Present). (February 2018) - Burke, Simeon R.
This article surveys post-1945 scholarly attempts to interpret Jesus' command to 'render to Caesar the things of Caesar and to God the things of God' (Mk 12.17; Mt. 22.21; Lk. 20.25). It suggests that part of the confusion surrounding the interpretation of this phrase lies not only in the disputed nature of the data, but also in the failure to clearly define the interpretive categories. This has resulted in contradictory interpretations being described with the same label, as well as scholars failing to notice similarities between the different readings. To this end, the following article attempts to more precisely outline the four major approaches to the command which have emerged since the Second World War (while also noting the various connections between some of these views): (1) exclusivist interpretations in which 'the things of God' nullify the 'the things of Caesar'; (2) complementarian readings in which the two elements are held to be parallel; (3) ambivalent readings that stress the ambiguity and open-ended nature of the utterance; and (4) subordinationist readings that seek to uphold both elements of the command while prioritizing the second element ('the things of God') over the first ('the things of Caesar'). The discussion then turns to considering four areas that might prove fruitful in future analysis of this command.